2011
DOI: 10.1186/1475-925x-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin resistant Staphylococcus aureus adhesion to human umbilical vein endothelial cells demonstrates wall shear stress dependent behaviour

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) is an increasingly prevalent pathogen capable of causing severe vascular infections. The goal of this work was to investigate the role of shear stress in early adhesion events.MethodsHuman umbilical vein endothelial cells (HUVEC) were exposed to MRSA for 15-60 minutes and shear stresses of 0-1.2 Pa in a parallel plate flow chamber system. Confocal microscopy stacks were captured and analyzed to assess the number of MRSA. Flow chamber parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Interestingly, our findings also suggest that bacterial adhesion rates to both static and sheared endothelial cells (i.e., 0 and 10 dynes/cm 2 , respectively) are similar. This is consistent with a recent study by Viegas et al () who showed that adhesion rates of methicillin‐resistant SA (MRSA) to human umbilical vein endothelial cells (HUVECs) were relatively similar for static and normal shear conditions (when corrected for differences in bacterial concentration near the cell surface due to increasing shear level), but were considerably higher for low shear conditions. This led the authors to conclude that SA preferentially adheres to the vascular endothelium in vivo at atheroprone sites characterized by low or disturbed shear stress (Viegas et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our findings also suggest that bacterial adhesion rates to both static and sheared endothelial cells (i.e., 0 and 10 dynes/cm 2 , respectively) are similar. This is consistent with a recent study by Viegas et al () who showed that adhesion rates of methicillin‐resistant SA (MRSA) to human umbilical vein endothelial cells (HUVECs) were relatively similar for static and normal shear conditions (when corrected for differences in bacterial concentration near the cell surface due to increasing shear level), but were considerably higher for low shear conditions. This led the authors to conclude that SA preferentially adheres to the vascular endothelium in vivo at atheroprone sites characterized by low or disturbed shear stress (Viegas et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, S . aureus adhesion to endothelium and endothelial ligands changes depending on the flow and shear stress [10, 30, 4850]. In experiments where we mimicked conditions in the vasculature, the anti-adhesive effect of deletions in ArlRS–MgrA cascade become even more apparent than in static assays.…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma pneumonia , a possible pathogen of PE, 30 , 31 is suspected to be associated with the development of subsequent AA because of cross-reactivity of the human heat shock protein with the immune response to bacterial antibodies 32 or because of increased adventitial inflammation, inhibition of TIMP-1 activity, and increased collagen degradation. 33 Methicillin-resistant Staphylococcus aureus (MRSA), a severe cause of empyema, was reported to be associated with atherosclerosis 34 ; thus, patients with MRSA-induced empyema may be at a higher risk of AA. There are 2 potential mechanisms of PE inducing IA.…”
Section: Discussionmentioning
confidence: 99%